Assessing vegetation reestablishment on disturbed high mountain lakeshores following historic dam removal in Rocky Mountain National Park, Colorado, USA - Goodrich, Amy C., author; Paschke, Mark, advisor; Meiman, Paul, advisor; Steingraeber, David A., committee member; Jonas-Bratten, Jayne, committee member (Colorado State University. Libraries, 2016)
Dam removal has entered the public spotlight in recent years, due to growing safety, economic, and environmental concerns related to dams. Removal is increasingly seen as a way to address not only the risks associated with aging and/or obsolete dams, but also as a tool for ecological restoration. In 1982, then-79-year-old Lawn Lake Dam in Rocky Mountain National Park failed, resulting in three deaths, and extensive monetary damages and destruction of natural resources within the Park. This was followed by a policy decision to remove three dams in the Park between 1988 and 1990, returning the former reservoirs to their previous natural lake water levels, and re-exposing nearly 13 hectares of scoured shoreline, completely denuded of vegetation by approximately 80 years of inundation. The disturbed lakeshore areas were left to undergo passive restoration. In the years immediately following dam removal, one short-term (3 year) revegetation study was conducted at Lawn Lake, and informal observational data were gathered by NPS personnel at a handful of plots established at the disturbed lakeshores of Bluebird, Sandbeach, and Pear Lakes. However, no further published analyses of data were made available, and until 2014 the vegetation at these lakeshores had not been surveyed to determine longer-term effects of damming and dam removal to reestablished vegetation. The goal of this study was to identify any persisting effects of historic damming and subsequent dam removal on vegetation characteristics such as species richness and diversity and community composition in the previously submerged lake margin areas surrounding the formerly dammed lakes, as well as the more elevated surrounding areas that had not been inundated. To do this, in July to September of 2014 I conducted surveys of vascular plant cover by species in 150 plots at nine high mountain lakes, including the four formerly dammed lakes and five undammed reference lakes. Site-specific environmental variables slope, aspect, elevation, elevation above current waterline, and soil texture were recorded at each plot. Plots were categorized as “elevated” or “lake margin” based on an elevation cutoff from the current waterline, to separate plots that had been previously submerged at dammed lake sites from more elevated sites that had not. I analyzed data from plots in each category for the effect of lake type (formerly dammed or reference) by fitting linear mixed models to species richness and diversity response. I performed a hierarchical cluster analysis that identified eight distinct vegetation communities, and performed non-metric multi-dimensional scaling (NMS) to explore relationships between vegetation community composition and site-specific measured environmental variables. No significant differences in vegetation characteristics of the elevated areas were found between formerly dammed and reference lakes. In previously submerged areas of formerly dammed lakes, however, species richness was significantly higher, compared to the similarly-located lake margin areas surrounding reference lakes (+3.361, χ2=8.919, p-val=0.003). All eight identified vegetation communities occurred at both formerly dammed and reference lakes. Slope and elevation were the measured environmental variables most strongly correlated with NMS axes (cumulative r2 values of 0.18 and 0.086), indicating that they are the most influential measured environmental variables in structuring plant communities at these study sites.